Visitor capacity of Kerachut Beach, Penang National Park, Malaysia - Ajuhari, Zamru (2022)
The modern-day visitor capacity frameworks address the importance of indicators and standards of quality in defining and managing visitor capacity. This notion is investigated in this study in a three-stage research process to determine the potential indicators, indicators of quality, and standards of quality for visitor capacity of Kerachut Beach, Penang National Park, Malaysia. The first stage of the research process is to determine the potential indicators. Forty-five visitors and nine stakeholders were asked a series of questions (open and closed-ended) concerning the resource, social and managerial conditions of Kerachut Beach. Six hundred ninety responses were recorded, representing three dimensions of visitor capacity. Eight potential indicators were determined and carried out in the second stage of the research process. The second stage of the research process is to determine the indicators of quality. The survey was carried out online via Microsoft Forms Platform and yielded 320 respondents. Indicators of quality were determined using the attitude that was plotted onto the Belief Evaluation Matrix. At this point, six indicators of quality were determined that respondents held disfavor attitudes concerning their experiences at Kerachut Beach. The third stage of the research process determines the standard of quality that defines the visitor capacity for Kerachut Beach. In this stage, a visual research approach was employed. Respondents were asked to evaluate the computer-edited photographs showing a range of conditions based on four evaluative dimensions: acceptability, preferability, acceptability to others, and management actions. Findings revealed that the standard of quality for the amount of litter on Kerachut Beach ranges from the P.I 2.6 to P.I 4.8, or 5.2% to 8.8% of litter accumulated in the 500m2 area. In addition, the standard of quality for the number of people on the beach ranges from 56 to 82 people at one time (PAOT). Regarding the campsite, the standard of quality ranges from 33 to 52 PAOT. Meanwhile, the standard of quality for the length of root exposure ranges from 165cm to 335cm. The standard of quality for the length of gully surfaces was 230cm to 325cm. Lastly, the standard of quality, the number of unusable toilets ranges from 1 to 4 unusable toilets at one time. Based on the findings, it could be helpful for the authority to incorporate the findings into visitor capacity management in Penang National Park to help maintain the quality of the park's natural resources and visitor experience.